TANCLICO: Tools for the Analysis of Inter-departmental Clinical Communications - Pinciroli, F.; Crippa, F.; Combi, C.; Reni, G.; Fava, D. (Methods of Information in Medicine, 2000)
Patient care management provided by healthcare organizations is complex, involving many different care providers. The information exchange between providers concerns a varying and considerable number of actors and a high transmission load. Based on models, used to characterize specific features of work processes, we propose a new method able to analyze and represent clinical communications inside hospitals. Software has been developed, providing tools for storing and retrieving information resulting from clinical communications. The method, together with data collected in actual situations, may constitute useful tools for health information systems developers.
Keywords: Clinical Inter-departmental Communication; Hospital Information System; Organizational Models